Environmental Sustainability Based on Natural Heritage Conservation and Resource Management in Tourist Objects in the Ampiang Parak Conservation Area - Firdaus Firdaus; Harfiandri Damanhuri; Aprizon Putra; Suparno Suparno; Arlius Arlius (Postgraduate School, Universitas Negeri Padang, 2024)
This research aims to analyze aspects of environmental sustainability based on natural heritage conservation and resource management at the coastal tourist attraction of Nagari Ampiang Parak, Pesisir Selatan Regency. Researchers carried out research through the use of qualitative methods using purposive sampling techniques. Techniques for collecting data were carried out through observation, interviews, and documentation. The process of testing data validity uses source triangulation analysis, namely data reduction, data presentation process, and conclusion. The turtle beach destination is said to be environmentally sustainable in terms of natural heritage conservation and resource management. The results of the research show that management of natural heritage conservation is not yet optimal, information media such as sites do not yet exist, resource management is not yet optimal because the destination does not yet have renewable energy, does not yet have guidelines for monitoring the reduction in water use and does not yet have data and reports on water quality.